Magnetic properties of polymeric acrylic acid hydrogel dosimeter for radiotherapy applications - Belal Moftah; Khalid A. Rabaeh; Akram A. Moussa; Md Abdullah Al Kafi; Abdullah S. Bani Issa (Scientific Reports)
Abstract The present study introduces the first magnetic characterization of a hydrogel dosimeter comprising acrylic acid synthesized within a polyvinyl alcohol matrix. The study aims to accurately assess ionizing radiation dose distributions, making it a valuable tool for radiotherapy treatment. The hydrogel was irradiated to a 1–60 Gy dose range using a medical linear accelerator with dose rates of 100–600 MU/min and radiation beam energies of 6, 10, and 15 MV. The developed dosimeter was synthesized by irradiation-triggered polymerization, and the polymerization degree was indirectly quantified by monitoring the positive alterations in the nuclear magnetic resonance spin‒spin relaxation rate. The polymeric hydrogel dosimeter demonstrated an exceptional dose response with an NMR sensitivity of 0.26 Gy⁻¹s⁻¹, which is 20 times more than the sensitivity of the same gel when measured optically in our previous study. Moreover, it exhibited consistent performance regardless of the beam energy or dose rate.